Finance and Development, December 1987. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1987)
This paper discusses the structural adjustment in low-income countries. In the first 20 months of its operations, the IMF's structural adjustment facility (SAF) has provided concessional financial assistance to support the balance-of-payments adjustment efforts of 21 low-income member countries. Most SAF arrangements have supported policy reform programs that have also received support under other IMF facilities. The fundamental concept underlying the SAF is the notion that growth and adjustment are mutually reinforcing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet